Development of chitosan/potato peel polyphenols nanoparticles driven extended-release antioxidant films based on potato starch. (March 2022) - Ma, Yajuan; Zhao, Hongqian; Ma, Qianyun; Cheng, Dewei; Zhang, Yufan; Wang, Wenxiu; Wang, Jie; Sun, Jianfeng
Abstract: An extended-release antioxidant film was prepared by starch, potato peel polyphenols (PP), and chitosan nanoparticles (CNP) to study the mechanical, hydrophobic properties and antioxidant activity of composite films. Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) were used to investigate the interactions and compatibility of PP, CNP-PP, and the film substrates. Scanning electron microscopy (SEM) was used to analyze the microstructures of the films. The release of PP in 10% and 50% (v/v) ethanol simulants was also examined. The results indicated that the incorporation of PP or CNP-PP into the starch film (S) increased their opacity and also improved their hydrophobicity. XRD and SEM revealed that the elongation at break increased significantly (p < 0.05), while the tensile strength decreased with the addition of CNP-PP, which were attributed to the reduced crystallinity and agglomerates distributed onto the film surface, respectively. Release studies revealed that the S + CNP-PP film exhibited an extended-release behavior of the encapsulated PP for 1440 min, compared to the burst release in the S + PP film, and the release kinetics was well fitted by the Fick's diffusion model. Moreover, the S + CNP-PP film showed excellent antioxidant activity and could inhibit the oxidation of cheese. Therefore, the extended-release antioxidant film has potential applications in food packaging for extending food shelf-life. Graphical Abstract: ga1 Highlights: Chitosan nanoparticles (CNP)/potato peel polyphenols (PP) extended-release antioxidant films were prepared. CNP-PP enhanced the flexibility and hydrophobicity of composite films. The addition of CNP decreased the release rate of PP. The Fick diffusion model well fitted the release kinetics of PP in the 10% and 50% ethanol simulants. The composite film exhibited excellent antioxidant activity.